Pengaruh Model Problem Based Learning (PBL) pada Mata Pelajaran PPKn terhadap Karakter Disiplin Murid SD Inpres Kampung Parang Kecamatan Bajeng Barat Kabupaten Gowa - Muh Iqram Marlis; Syamsuriyanti Syamsuriyanti; Nur Salam (Journal on Education, 2024)
The purpose of this research is to determine the influence of the problem based learning model for PPKN subjects on the disciplined character of students at SD Inpres, Kampung Parang, West Bajeng District, Gowa Regency. This type of research is ex post facto research with a one-group pretest-posttest design. The sample used was 22 grade IV students at SD Inpres Kampung Parang. The instrument used to collect data was a questionnaire. The results of this research show that the data was analyzed using descriptive analysis and inferential analysis. Data were analyzed using descriptive statistical analysis techniques. It was found that the average (mean) pretest value was 70.91 while the average (mean) posttest was 86.09, the average value on the posttest was higher than the average value on the pretest. In hypothesis testing using the independent sample t-test, where the data tested is hypothesis testing carried out on the pretest and posttest results, based on the management of the hypothesis results obtained sig (2.Tailed) = 0.000, meaning that H0 is rejected because sig (2.Tailed ) < α or (0.000 < 0.05). H1 is accepted as sig (2.Tailed) > α or (0.148). In the T test analysis, Sig < ttable or (0.148 < 1.686). Testing this hypothesis, it can be concluded that there is an influence in the Problem Based Learning (PBL) model on the discipline character of students at Inpres Elementary School, Kampung Parang, West Bajeng District, Gowa Regency.